Handling Of Shortage Container In Provision Of Export Container In Pt. Meratus Lines Branch Makassar - Yeti Komalasari (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2021)
Export activity is a source of incoe of companies and countries that can increase revenue. In order for the implementation of export activities in PT Meratus can ru smoothly, the company implements the system in service for customer satisfication. During carry out on job training in PT Meratus still in findng the consignee that does not return the container in a timely manner. This causes a shortage in the depo. Delays in container returns will hamper export activities at PT Meratus Line where shipment in the form of exports is a large load of actvities that can incrase the income of a company. From the result of analysis and discussion of the research, it is seen that the efforts of PT Meratus have overcome it optimally because it s very necessary once the efforts of various parties for export activities within the company is successful, and can incrase corporate ernings. If the above process is done then export process will run smoothly.